Metopoplax ditomoides (A. Costa, 1843), aglomeraciones invernales y picaduras a niños (Hemiptera, Heteroptera, Oxycarenidae) - Manuel Baena; Manuel Moro (Boletín de la Asociación Española de Entomología)
Metopoplax ditomoides (A. Costa, 1843), winter outbreaks and bites to children (Hemiptera, Heteroptera, Oxycarenidae)